Fibrewise ω-compact and locally ω-compact spaces. Issue 7 (3rd October 2021) - Yousif, Y. Y.
Abstract: The goal of this article is to construct fibrewise w-compact (resp. locally w-compact) spaces. Some related results and properties of these concepts will be investigated. Furthermore, we investigate various relationships between these concepts and three classes of fibrewise w-separation axioms.